2018
DOI: 10.1016/j.bbamem.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Rhodomyrtone (Rom) is a membrane-active compound

Abstract: Particularly in Asia medicinal plants with antimicrobial activity are used for therapeutic purpose. One such plant-derived antibiotic is rhodomyrtone (Rom) isolated from Rhodomyrtus tomentosa leaves. Rom shows high antibacterial activity against a wide range of Gram-positive bacteria, however, its mode of action is still unclear. Reporter gene assays and proteomic profiling experiments in Bacillus subtilis indicate that Rom does not address classical antibiotic targets like translation, transcription or DNA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 51 publications
0
38
0
1
Order By: Relevance
“…To identify commonalities of the physiological impact of allicin to that of other antibacterial agents, we compared the proteomic response to allicin to a response library containing 44 proteomic responses of B. subtilis to known antimicrobial agents . Regarding the number of induced proteins, with 56 marker proteins, allicin evoked the most complex response in B. subtilis among the tested compounds.…”
Section: Resultsmentioning
confidence: 99%
“…To identify commonalities of the physiological impact of allicin to that of other antibacterial agents, we compared the proteomic response to allicin to a response library containing 44 proteomic responses of B. subtilis to known antimicrobial agents . Regarding the number of induced proteins, with 56 marker proteins, allicin evoked the most complex response in B. subtilis among the tested compounds.…”
Section: Resultsmentioning
confidence: 99%
“…These indicated that the compound disturbed the intracellular bacterial protein homeostasis. Furthermore, Saeloh et al (2018) demonstrated that rhodomyrtone caused delocalization of membrane proteins correlated to the cell size and shape defects in B. subtilis and S. aureus (Saising et al 2018;Sianglum et al 2018). Two important cell division proteins, DivIVA and FtsA were known to associate with FtsZ during the septum formation as a final step of cell division.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, rhodomyrtone was clearly demonstrated to be a membrane-active compound. Following the treatment, S. aureus membrane potential decrease immediately at low doses resulted in releasing of ATP and cytoplasmic protein without pore-formation effect (Saising et al 2018). Other workers demonstrated the increase in membrane fluidity and the collapsed membrane potential in Bacillus subtilis as well as the relocalization of seven membrane proteins (FtsA, DivIVA, MinD, PlsX, MreB, MurG and SdhA), trapping within the region of increased lipid fluidity (RIF) (Saeloh et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Saeloh et al (2018) demonstrated that rhodomyrtone caused delocalization of membrane proteins correlated to the cell size and shape defects in B. subtilis and S. aureus (Saising et al 2018;Sianglum et al 2018). Two important cell division proteins, DivIVA and FtsA were known to associate with FtsZ during the septum formation as a nal step of cell division.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, rhodomyrtone was clearly demonstrated to be a membrane-active compound. Following the treatment, S. aureus membrane potential decrease immediately at low doses resulted in releasing of ATP and cytoplasmic protein without pore-formation effect (Saising et al 2018). Other workers demonstrated the increase in membrane uidity and the collapsed membrane potential in Bacillus subtilis as well as the relocalization of seven membrane proteins (FtsA, DivIVA, MinD, PlsX, MreB, MurG and SdhA), trapping within the region of increased lipid uidity (RIF) (Saeloh et al 2018).…”
Section: Introductionmentioning
confidence: 99%